Potret Kekerasan dan Perlindungan Anak dalam Perspektif Sosio-Yuridis - Sukamto, Sukamto (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: Children are human beings who have not reached adulthood. They have right to live safely and comfortably and to avoid violence. In reality, it is often encountered a violence on children. There are several factors of violence against children, namely: first, a âperceptionâ that sees the status of parents who occupy an important role in social life of children. The relationship between children and parents has a strong emotional bond; second, with regard to the above âperceptionâ, of course, it has a very complex implication at all, including the unbalanced relationship between children and parents, the emergence of violence against children by their own parents; third, a system and tradition, that have been embraced by the paternalistic people, becomes the reason to put the childrenâs status under that of the parents. To provide protection for children, the Indonesian government has made Undang-Undang on children protection, as outlined in Undang-Undang No. 23 tahun 2002. It can generally be classified as follows: first, the right of survival; second, the right of growth and development; third, the right to get protection includes protection against discrimination, abuse and neglect, protection for children without family and protection for refugee children; and fourth, the right of participation which includes the right to express their opinion/view in all matters relating to the fate of the children.Keywords: Violence, protection, child, socio-juridical